2017
DOI: 10.1093/mnrasl/slx174
|View full text |Cite
|
Sign up to set email alerts
|

Formation of precessing jets by tilted black hole discs in 3D general relativistic MHD simulations

Abstract: Gas falling into a black hole (BH) from large distances is unaware of BH spin direction, and misalignment between the accretion disc and BH spin is expected to be common. However, the physics of tilted discs (e.g., angular momentum transport and jet formation) is poorly understood. Using our new GPU-accelerated code H-AMR, we performed 3D general relativistic magnetohydrodynamic simulations of tilted thick accretion discs around rapidly spinning BHs, at the highest resolution to date. We explored the limit whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
334
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(360 citation statements)
references
References 54 publications
14
334
2
Order By: Relevance
“…Fragile et al [55] found that such a thick disc with an initial tilt angle of β 0 = 15 • did indeed undergo solid-body precession as predicted by the analytic theory, at a precession frequency consistent with Equation (16). Recently Liska et al [120] repeated this setup, but were able to achieve higher resolution, particularly around the poles of the grid. This enabled them to resolve jets, which they found to precess with the thick disc (see Fig 12).…”
Section: Numerical Simulationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Fragile et al [55] found that such a thick disc with an initial tilt angle of β 0 = 15 • did indeed undergo solid-body precession as predicted by the analytic theory, at a precession frequency consistent with Equation (16). Recently Liska et al [120] repeated this setup, but were able to achieve higher resolution, particularly around the poles of the grid. This enabled them to resolve jets, which they found to precess with the thick disc (see Fig 12).…”
Section: Numerical Simulationsmentioning
confidence: 94%
“…Such grid-based simulations therefore provide the best tests for analytic theory. [120] (reproduced from said paper) at two times (as labelled; t g = R g /c). We see precession of both thick disc (blue/green) and jet (yellow/red).…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…The alignment of the jet with the angular momentum vector of the disk is the simplest assumption and it has some observational support from the measure- ments of the X-ray binary system XTE J1550−564 (Steiner & McClintock 2012). Recent general relativistic magnetohydrodynamic simulations of tilted accretion disks around black holes have shown that the disk and the jet are generally well-aligned (Liska et al 2018). However, Bardeen-Petterson effect can align the jet and the disk with the black hole spin axis at small radii (less than a few R g ) rapidly compared to the viscous time scale in which the whole diskjet system aligns with the black hole spin axis (Liska et al 2019b).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Typically, these neglect radiative processes and the interface between the disc and hot flow (e.g. Liska et al 2017). Until better simulations are available, we instead use a parametrized prescription where f visc (r) = Br −m f kep (r) (ID11).…”
Section: T H E P Ro Pag At I N G F L U C T Uat I O N S M O D E Lmentioning
confidence: 99%
“…This process can reproduce the observed double-broken power-law shape of the low/hard state PSD, while Arévalo & Uttley (2006; hereafter AU06) also show that this behaviour is necessary and sufficient to produce the observed linear rms-flux relation. The correlated QPO can also be produced from the same geometry if the entire hot flow undergoes LenseThirring precession due to its misalignment with the black hole spin axis (Fragile & Meier 2009;Ingram, Done & Fragile 2009;Liska et al 2017). These propagating fluctuation/Lense-Thirring precession models have quantitatively fit the data from XTE J1550−584 during its spectral transition, with the inner radius of the thin disc changing from ∼60 to 12R g (ID11; Ingram & Done 2012a, hereafter ID12a), while also correctly predicting the modulation of the iron line energy on the QPO period (Ingram & Done 2012b;Ingram et al 2016).…”
Section: Introductionmentioning
confidence: 99%